1989
DOI: 10.1007/bf01739655
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia — a disease of young single males?

Abstract: The later age at onset of schizophrenia in females, reported in the literature, led to a study of transnational case register data and of a cohort of all patients admitted to hospital for the first time with a non-affective functional psychosis from a defined catchment area. The preliminary analysis of the first representative sample of 86 patients showed that at the time of first admission with a diagnosis of schizophrenia (according to different diagnostic definitions) as well as at the time of onset of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 6 publications
0
5
0
3
Order By: Relevance
“…19 It formally appeared in PubMed literature in 1989 in a pioneering work by Huber and Gross, 20 who, influenced by Mayer-Gross' observations, first described basic symptoms (BS) in the 1960s and initiated the first prospective early detection study in the 1980s. In 1989, Häfner et al, 21 for the first time, examined the prodrome on a representative population of 232 first-admitted psychosis patients of a large catchment area in and around Mannheim, Germany, in the ABC (Age, Begin, and Course of Schizophrenia) study. 22-25 It was shown that in 73% of all the patients, the disorder began with a prodromal phase, which lasted, on average, 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…19 It formally appeared in PubMed literature in 1989 in a pioneering work by Huber and Gross, 20 who, influenced by Mayer-Gross' observations, first described basic symptoms (BS) in the 1960s and initiated the first prospective early detection study in the 1980s. In 1989, Häfner et al, 21 for the first time, examined the prodrome on a representative population of 232 first-admitted psychosis patients of a large catchment area in and around Mannheim, Germany, in the ABC (Age, Begin, and Course of Schizophrenia) study. 22-25 It was shown that in 73% of all the patients, the disorder began with a prodromal phase, which lasted, on average, 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…The present study includes many individuals who were never hospitalized but who were rather exposed to modern treatment regimens, together with inpatients, yet their marital rate is no different either from those reported in a study confined to outpatients alone (16) or reported at the turn of the century (17). Failure to marry may more reflect the underlying schizophrenic illness (2,15,18,20), with premorbid personality difficulties and symptoms such as flattened affect and avolition preempting the development of relationships leading to marriage. The earlier age at onset of illness in males, in conjunction with their greater negative symptoms, may further reduce the likelihood of marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia and other psychotic disorders are increasingly thought of as neurodevelopmental disorders, where multiple hits accumulate during critical periods of central nervous system (CNS) development to cause the disorders. The majority of patients with schizophrenia began with a prodromal phase characterized by subclinical symptoms of the disorder, which we will refer to hereafter as a state of clinical high risk for psychosis (CHR) [1,2,3,4]. In some studies, 22% of those meeting the criteria for CHR convert to a psychotic disorder at one year follow-up, as compared to 0.015% in the general population [5].…”
Section: Introductionmentioning
confidence: 99%